Skip around the year - Fisher, Aileen; Fiammenghi, Gioia (New York, Crowell, 1967)
A collection of poems about the different special days during the year, including patriotic holidays, religious celebrations and such days as Mother's Day.
Keywords: Holidays; Holidays; Holidays; Holidays